HIGH -PERFORMANCE WORK PRACTICES AND EMPLOYEE ATTITUDES: EVIDENCE FROM HOTEL INDUSTRY IN SRI LANKA - Saravanabawan, A. (University of Jaffna, 2017)
In this contemporary world, most of the organizations understand the importance of managing human resources effectively and efficiently to become successful. Many Previous researches have established a significant relationship between High performance Human resource (HR) practices and firm level and individual level outcomes. Few studies have considered the important role of employee perceived HR practices and outcome of high performance HR practices and its mediating roles. To address the recent growing interest in the literature for an investigation of this nature, this study was conducted investigating the relationship between high-performance work practices and employee attitudes in the hotel industry of Sri Lanka. Questionnaire was used to collect the data. Initially discussion was conducted with 200 employees who voluntarily participated in this study from Hotel sector, finally 175 participants agreed to fill out the questionnaire. Of the selected sample 150 questionnaires was complete and usable for this study. Correlation and regression analysis was performed to test the hypothesized relationship. Results of the study showed that high -Performance work practices positively related with intention to remain with organization, further study found positive relationship between employees’ perceptions of high-performance work practices and affective commitment; furthermore, study found that affective commitment mediated the relationship between high performance work practices and intention to remain with organization. On the basis of these findings, managerial implications of the study and future research direction were highlighted.
Keywords: high - performance work practices; attitudes; commitment; hotel industry; Sri Lanka